Connection between winter Arctic sea ice and west Tibetan Plateau snow depth through the NAO. (22nd June 2020) - Chen, Yuhang; Duan, Anmin; Li, Dongliang
Abstract: The relationship between changes in Arctic sea ice and the mid‐latitude climate has been receiving increasing attention. As the highest and largest topography in Asia, the possible link between the west Tibetan Plateau snow depth (WTPSD) and the Arctic sea ice was investigated based on observational data and model simulations. The results indicate that a consistent variation between the WTPSD and the seesaw sea ice pattern in the Barents‐Nordic Sea and Labrador Sea (BLSIC) exists during boreal winter, and both the WTPSD and BLSIC are negatively correlated with the North Atlantic Oscillation (NAO) index. During the negative phases of the NAO, an anomalous Rossby wave train propagates from the North Atlantic to the north of the Arabian Sea, inducing cyclonic anomalies in the mid‐troposphere and enhancing water vapour transportation onto the TP, which is conducive to in situ snow accumulation. Furthermore, composite analysis and AGCM numerical experiments demonstrate that such an anomalous BLSIC pattern can in turn reinforce the negative phase of the NAO in strength, facilitating the propagation of the mid‐tropospheric Rossby waves to north of the Arabian Sea and hence an above normal WTPSD. Therefore, the variation in WTPSD is influenced by the direct effect of the NAO and additional feedback from BLSIC, which hints a potential cryospheric connection between the TP and the Arctic. Abstract : During the boreal winter, the increased west Tibetan Plateau (TP) snow depth (SVDsd‐pc1) is related to the Arctic sea ice pattern of increased sea ice in the Barents‐Nordic Sea and decreased sea ice in the Labrador Sea (SVDsic‐pc1). Both the west TP snow depth and Arctic sea ice are commonly driven by the negative phase of North Atlantic Oscillation (NAO). In addition, the feedback of the Arctic sea ice can promote the effect of NAO on the west TP snow depth, which suggests a cryospheric connection between the TP and the Arctic.